The end of capitalism as a concept: Towards a new political economy for understanding monetary societies in the biosphere - Tiago Cardao-Pito (Innovation and Green Development)
Political economy has two major concepts of capital. In one, capital is defined as money. Adam Smith proposed the other, which considers capital as anything that has a role in the creation of wealth even if peripheral. It includes, for instance, machines, the biosphere (“nature capital” or “natural capital”), and even human beings (“human capital”). The concept of capitalism is generally derived from Smith's overinclusive concept of capital. This led to ambiguity and tautology. However, the pre-Smith concept of capital does not require the concept of capitalism. By removing non-monetary elements from the concept of capital, this study reaches an alternative ‘monetary society in the biosphere’ concept, which avoids confusion regarding monetary and non-monetary flows. This new concept integrates the economic and societal production in the biosphere. Furthermore, it recognizes that various monetary flows can be detrimental to ecological crises. Abandoning the concept of capitalism can contribute to conceptual precision in addressing the political economy of societal, environmental, and green development phenomena.